Social contact, practice, organization and technical knowledge: Experiences of music students in the course of the COVID-19 pandemic - Spahn, Claudia; Immerz, Anna; Hipp, Anna Maria; Nusseck, Manfred (Frontiers in Psychology, 2022)
For music students especially, the COVID-19 pandemic has had a great impact, forcing them to adapt to certain coronavirus regulations laid down by the state. In this study, the experiences of music students in three consecutive semesters under different coronavirus-related conditions are investigated. At the end of three semesters, the lockdown semester (SS (Summer Semester) 2020), a partially opened semester (WS (Winter Semester) 2020/21) and a mostly opened semester (SS (Summer Semester) 2021), a total of 152 music students were asked to fill in an online survey. A mixed-methods approach has been used, with results showing that the qualitative statements of the students support the quantitative data. The results demonstrate that self-regulated learning improved during the COVID-19 pandemic, especially during the lockdown semester, through new time management and focused practice with regular breaks. Furthermore, it has been shown that new technological knowledge has emerged, which has evolved over the course of the three semesters. Also, when offering blended learning formats, educators must take into account organizational aspects such as spatial distances and locations. Overall, the results of the study show that the experiences of the music students from the semesters during the COVID-19 pandemic provide constructive starting points for future teaching.